Mechanistic Insight into PPARγ and Tregs in Atherosclerotic Immune Inflammation - Gao, Zhao; Xu, Xinrui; Li, Yang; Sun, Kehan; Yang, Manfang; Zhang, Qingyue; Wang, Shuqi; Lin, Yiyi; Lou, Lixia; Wu, Aiming; Liu, Weijing; Nie, Bo (Frontiers in Pharmacology, 2021)
Atherosclerosis (AS) is the most important pathological basis of cardiovascular diseases, and it is the main cause of acute cardio-cerebrovascular diseases such as acute myocardial infarction and cerebral apoplexy. As an immune inflammatory disease, the pathogenesis of atherosclerosis involves endothelial cell dysfunction, lipid accumulation, foam cell formation, vascular smooth muscle cell migration and inflammatory factors infiltration, etc. Peroxisomal proliferator-activated receptor γ (PPARγ), a kind of nuclear receptor, plays an important role in the lipid metabolism, inflammation, and apoptosis by regulating cholesterol efflux and inflammatory factors. Activated PPARγ can implement anti-atherosclerosis effect by inhibiting the expression of various inflammatory factors, improving endothelial cell function, and restraining the proliferation and migration of vascular smooth muscle cells (VSMC). Regulatory T cells (Tregs) are the only T lymphocyte subsets that have a completely negative regulatory effect on the autoimmune response. They perform a critical role in suppressing excessive immune response and inflammatory reaction, widely participating in AS foam cells formation, plaque rupture and other processes. Recent studies have shown that activation of PPARγ plays an anti-atherosclerosis role by promoting the recruitment of Tregs and reducing inflammation. In this review, we explain the pathological mechanism from the perspective of atherosclerosis and immune inflammation, focus on basic research and clinical trials to introduce the role of PPARγ, Tregs and their combined effects in inhibiting atherosclerotic inflammation, explore new ideas for the treatment of AS and plaque stabilization, and establish the foundation for the development of natural PPARγ agonists with Tregs recruitment.